Plant–microorganism–soil interaction under long-term low-dose ionizing radiation - Zeng, Guoqiang; Wen, Yingzi; Luo, Chuyang; Zhang, Yihong; Li, Fei; Xiong, Chao (Frontiers in Microbiology, 2024)
As the environmental nuclear radiation pollution caused by nuclear contaminated water discharge and other factors intensifies, more plant-microorganism-soil systems will under long-term low-dose ionizing radiation (LLR). However, the regulatory mechanisms of the plant-microorganism-soil system under LLR are still unclear. In this paper, we study a system that has been stably exposed to low-dose ionizing radiation for 10 years, and investigate the response of the plant-microorganism-soil system to LLR based on the decay of the absorbed dose rate with distance. The results show that LLR affects the carbon and nitrogen migration process between plant-microorganism-soil through the "symbiotic microbial effect". The increase in the intensity of ionizing radiation led to a significant increase in the relative abundance of symbiotic fungi such as Ectomycorrhizal fungi and Rhizobiales, which is accompanied by a significant increase in soil lignin peroxidase (LiP) activity, the C/N ratio and C%. Meanwhile, enhanced radiation intensity causes adaptive changes in the plant functional traits. This study demonstrates that the "symbiotic microbial effect" of plant-microorganism-soil systems is an important process in terrestrial ecosystems in response to LLR.